Combining combinatorial optimisation and planning to solve the non-recurrent traffic jam problem. (24th April 2023) - Laalaoui, Yacine
In this paper, we solve the non-recurrent traffic jam problem. This problem includes n stopped vehicles where all of them share the same destination. We divided the problem into three subproblems namely: pathfinding, min-max, and planning. Pathfinding consists of determining the list of roads and paths that will be used to solve the jam situation. Min-max is an optimisation problem, and it consists of assigning the overall vehicles in the jam situation to the list of roads leading to the final destination. Planning consists of finding the list of moves by each vehicle that will lead to the clearance of the jam situation. The proposed approach can be used to solve arisen jam situations at any time in the road network, and it has potential use in handling emergency situations. Experimental results using CPLEX and Metric-FF solvers on randomly-generated problem instances provide computational evidence of the applicability of the described approach.